2018
DOI: 10.1021/acs.jpcc.8b02541
|View full text |Cite
|
Sign up to set email alerts
|

Operando Time-Resolved X-ray Absorption Fine Structure Study for Pt Oxidation Kinetics on Pt/C and Pt3Co/C Cathode Catalysts by Polymer Electrolyte Fuel Cell Voltage Operation Synchronized with Rapid O2 Exposure

Abstract: The oxidation of a cathode catalyst surface is one of the major factors for cathode catalyst degradation under polymer electrolyte fuel cell (PEFC) operating conditions; however, the oxidation kinetics of Pt cathode catalysts in a membrane electrode assembly with O2 has not been investigated. We have investigated operando Pt LIII-edge time-resolved X-ray absorption fine structure analysis for the Pt oxidation processes on Pt/C and Pt3Co/C cathode catalysts controlled by transient PEFC voltage operation (0.4 V … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…It should be noted that the white line for A-Pt greatly increased at 0.9–1.0 V vs RDE, which corresponds to the potential region of Pt surface oxidation, whereas that for A-Pt-Gd­(5/1) did not increase at the same potential. These results strongly support the hypothesis that the addition of Gd inhibited oxidation of the Pt nanoparticles, which would be expected to enhance the rates of Pt–O bond formation and cleavage on the Pt surface , and thus improve the ORR activity.…”
Section: Resultssupporting
confidence: 84%
“…It should be noted that the white line for A-Pt greatly increased at 0.9–1.0 V vs RDE, which corresponds to the potential region of Pt surface oxidation, whereas that for A-Pt-Gd­(5/1) did not increase at the same potential. These results strongly support the hypothesis that the addition of Gd inhibited oxidation of the Pt nanoparticles, which would be expected to enhance the rates of Pt–O bond formation and cleavage on the Pt surface , and thus improve the ORR activity.…”
Section: Resultssupporting
confidence: 84%
“…Quick XAS can achieve 10-ms time resolution and can be applied to study dynamic or kinetic states in chemical and electrochemical reactions such as high rate delithiation behavior and nucleation process of nanoparticles [ 89 , 90 ]. Currently, the quick X-ray absorption spectroscopy has also been used in the electrocatalysis field to resolve the reconstruction of the catalysts within several seconds [ 91 , 92 ]. Pump-and-probe spectroscopy studies ultrafast electronic dynamics.…”
Section: Other Xas Applicationsmentioning
confidence: 99%
“…X-ray Computed Laminography (XCL) [140,141] has also proven to be a useful method of analysis; Saida et al [142] demonstrated the use of XCL in combination with X-ray Absorption Fine Structure (XAFS) [143] in the form of Laminography -XAFS to examine the cathode CL in 4D exposing Pt distribution before and after degradation. XAFS has also been demonstrated operando by Ozawa et al [144] who utilised this technique to explore the rate of Pt-O bond formation with potential. Recently, Yu et al demonstrated the use of Hard X-ray Photoelectron Spectroscopy (HAXPES) in order to examine sulphur poisoning of such Pt CLs [145].…”
Section: Figurementioning
confidence: 99%